The muscarinic system, cognition and schizophrenia. (August 2015) - Carruthers, Sean P.; Gurvich, Caroline T.; Rossell, Susan L.
Highlights: Schizophrenia is marred by debilitating cognitive impairments. Pharmacological interventions fail to effectively treat such cognitive symptoms. The central muscarinic system facilitates a number of cognitive processes. Substantial central muscarinic system abnormalities exist in schizophrenia. M1 and M4 receptor manipulation may provide means for effective treatment against symptoms. Abstract: An increasing body of evidence has implicated the central muscarinic system as contributing to a number of symptoms of schizophrenia and serving as a potential target for pharmaceutical interventions. A theoretical review is presented that focuses on the central muscarinic system's contribution to the cognitive symptoms of schizophrenia. The aim is to bridge the void between pertinent neuropsychological and neurobiological research to provide an explanatory account of the role that the central muscarinic system plays in the symptoms of schizophrenia. First, there will be a brief overview of the relevant neuropsychological schizophrenia literature, followed by a concise introduction to the central muscarinic system. Subsequently, we will draw from animal, neuropsychological and pharmacological literature, and discuss the findings in relation to cognition, schizophrenia and the muscarinic system. Whilst unifying the multiple domains of research into a concise review will act as a useful line of enquiry into the central muscarinic systems contribution to the symptoms of schizophrenia, it will be made apparent that more research is needed in this field.